Extent of application of CAATs in auditing - Md Nor, Nurul Safida; Mohamad, Amri (Faculty of Accountancy, Universiti Teknologi MARA (UiTM) Cawangan Kelantan, 2025)
Advancement of digital commerce industry and the rapid development of automated system such as big data, artificial intelligence, cloud computing, and robotics are what motivate businesses to adopt new technology (Verhoef et al., 2021). As technology advances and affects the business world, auditors need to implement and use technology-based audit approaches in their audit job. Auditors must embrace the technological world and use the technology as a tool in the audit procedures. Auditors who work in the public and private sectors, whether internal or external, use CAATs in numerous nations. CAATS or Computer-Assisted Audit Techniques can be outlined as the application of computer software in auditing activities in order to collect audit evidence and make it easy for auditors to analyse the data (Handoko et al., 2020). According to Abdul Ghani et al. (2022), CAATs are software programmers and methods that auditors (internal or external) use to process data in an entity's system while carrying out audit procedures. Auditors have used office tools which just scrape the surface of impressive tasks and procedures for years. As auditing becomes an essential component that measures a company's effectiveness, CAATs assist auditors in analysing and visualizing increasing amounts of data. Acceptance of CAATs in audit firms has many benefits. Purnamasari et al. (2022) stated that using computer-assisted audit techniques (CAATs) can increase audit effectiveness and efficiency for auditors.